The Interactive Relationship between the Formation Elements and their Implications in the Structure of the Television Image - دفاك, مصطفى عبيد (ALBAHITH ALALAMI, 2018)
The image of television dominates the cognitive and artistic motivations. It is the formulation of ideas and visions along with its documentary ability. It is the main element in television work as it is a story that is narrated in pictures. Therefore, attention to image building is a major point of gravity in the work structure as a whole. On the image is the element carrying all aesthetic and expressive values of news and information directly to the hints that work to stimulate and stir the imagination of the recipient to evoke mental images added to the visual images to deepen the meanings.All visual arts carry elements and components that follow in a particular pattern to give special meanings and specific connotations. However, a person is more responsive to the images resulting from a certain consistency of the surface, shape, and blocks of objects because this harmony creates a sense of pleasure while the lack of such harmony causes with discomfort and indifference or even dissatisfaction and dislike as Herbert Reid put it. Therefore, the harmony in the arrangement and organization of the elements of television image leads to the creation of the state of engagement and autism with them and thus accept television work as a unit. From these facts, this research, which deals with the plastic structure of television image, is launched in an analytical study of the television work (bioot alsafeeh)